2022-RA-1341-ESGO Minimally invasive versus open pelvic exenterationin gynecological malignancies: a propensity-matched survival analysis. (20th October 2022) - Bizzarri, Nicolò; Chiantera, Vito; Loverro, Matteo; Sozzi, Giulio; Perrone, Emanuele; Alletti, Salvatore Gueli; Costantini, Barbara; Gallotta, Valerio; Tortorella, Lucia; Fagotti, Anna; Fanfani, Francesco; Ercoli, Alfredo; et al.
Abstract : Introduction/Background: The primary endpoint of the present study was to compare the disease-free survival (DFS) of patients undergoing open versus minimally invasive pelvic exenteration (PE). Secondary endpoints cancer-specific survival (CSS) and peri-operative morbidity. Methodology: Multi-center, retrospective, observational cohort study. Patients undergoing anterior or total PE for gynecological cancer by minimally invasive and open approach between 2010–2021 were included. Positive para-aortic/inguinal lymph nodes and with distant metastases were excluded. A 1:2 propensity match analysis between patients undergoing minimally invasive and open PE was performed to equalized baseline characteristics. Results: 117 patients were included, 78 (66.7%) and 39 (33.3%) in the open and minimally invasive group, respectively. No significant difference in intra- and post-operative complications was evident between the two study groups (trend toward higher incidence of complications in open approach patients). Patients undergoing open PE received higher number of intra-operative transfusions (p=0.013). Median DFS was 17.0 months versus 17.0 months in open versus minimally invasive group, respectively (p=0.632). Median CSS was 30.0 months versus 26.0 months in open versus minimally invasive group, respectively (p=0.800). Positive surgical margins at final histology was the only significant factor influencing the risk of recurrence (HR:2.378, 95%CI 1.313–4.308) (p=0.004), while tumor diameter ≥50 mm at time of PE was the only significant factor influencing the risk of death (HR:1.833, 95%CI 1.080–3.111) (p=0.025). Conclusion: No survival difference was evident when minimally invasive was compared to open PE in patients with gynecological cancer. No difference in peri-operative complications, but higher intra-operative transfusion rate in open group, was evident.